KONSEP PERWALIAN PEREMPUAN DALAM PERNIKAHAN MENURUT SYEIKH MUHAMMAD ARSYAD AL-BANJARI DAN PROF. DR. WAHBAH AZ- ZUHAILI - Anwar Hafidzi; Norhaliza Norhaliza (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2023)
Wali is a person who has the right to marry a woman's husband according to Islamic law. Marriage guardians have a very important position, they can even determine whether a marriage is valid or not. Marriage without a legal guardian is null and void. The purpose of this research is to understand the concept of female guardianship in marriage. The results of the study showed that the concept of female guardianship in marriage according to the book of Sheikh Muhammad Arsyad Al-Banjari and the Book of Islamic Fiqh Wahbah Az-Zuhaili have similarities in terms of women's guardianship in marriage. In these two books the emphasis is on guardianship which takes precedence, namely the intimate guardian then the ab'ad guardian. The method used is by conducting qualitative research methods that focus on library research using literary sources such as manuscripts, books, journals, newspapers and other documents.